Multi-layer coaxial piezoelectric sensing fiber, preparation method thereof and flexible wearable fabric

Through coaxial wet spinning technology and in-situ reduction method, multi-layer coaxial piezoelectric sensing fibers were prepared, solving the problem of developing high-performance flexible piezoelectric sensing fibers in the existing technology, and achieving strong and stable piezoelectric sensing signal output, suitable for flexible wearable fabrics.

CN119824577AActive Publication Date: 2025-04-15JIANGSU KUANGDA AUTOMOTIVE TRIM CO LTD +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411960274.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-15
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

It is difficult to develop high-performance flexible piezoelectric sensing fibers in the prior art, and the signal output strength of the sensing fibers is relatively weak, and the application is limited.

Method used

Coaxial wet spinning technology is used to prepare multi-layer coaxial piezoelectric sensing fibers. Through the design of the core layer and shell layer, liquid metal composites are used as the inner electrode and nanosilver as the outer electrodes, and combined with in-situ reduction method and corona polarization treatment, the self-generated sensing performance of the fibers is achieved.

Benefits of technology

It overcomes the problem of airtight piezoelectric sensors with multi-layer film structures, and achieves stronger and more stable output of piezoelectric sensing signals, which is suitable for a wide range of applications of flexible wearable fabrics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824577A_ABST
    Figure CN119824577A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of piezoelectric materials, and particularly relates to a multilayer coaxial piezoelectric sensing fiber, a preparation method thereof and a flexible wearable fabric, and the preparation method comprises the following steps: S1, respectively preparing a core layer spinning solution and a shell layer spinning solution; s2, placing the core layer spinning solution and the shell layer spinning solution on a wet spinning device, and sequentially curing, drafting and winding to obtain a composite fiber with a core-sheath structure; s3, the composite fibers are soaked in a reducing agent solution, a large number of composite piezoelectric layers are formed on the surfaces of the composite fibers in a stacking mode, and conductive fibers of a multi-layer coaxial structure are obtained; s4, placing the conductive fiber in silicone oil, and performing corona polarization treatment on the middle composite piezoelectric layer by taking the core layer of the fiber as an inner electrode and the silver layer on the surface of the fiber as an outer electrode to obtain a self-generating sensing fiber; and step S5, blending the polydimethylsiloxane main agent and the curing agent, and carrying out packaging treatment to obtain the self-generating sensing fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of piezoelectric materials, and in particular relates to a multi-layer coaxial piezoelectric sensing fiber and a preparation method thereof, and a flexible wearable fabric. Background Art

[0002] Piezoelectric materials are new intelligent materials that can convert mechanical energy into electrical energy and can be used as highly sensitive sensors. Among them, lead zirconate titanate (PZT) piezoelectric ceramics have higher piezoelectric constants and electromechanical coupling coefficients than barium titanate, zinc oxide, etc., and are widely used in the manufacture of electronic devices such as transducers, hydrophones, transformers, speakers, etc. Traditional piezoelectric ceramics are mostly manufactured by dry pressing, tape casting and roll forming. Due to the high brittleness of ceramics, they cannot meet the requirements for the use of flexible sensing materials. The composite piezoelectric film material obtained by compounding piezoelectric ceramics and polymers has both a high piezoelectric constant and good flexibility, and is an effective means of preparing flexible sensing materials. However, the addition of a large amount of piezoelectric ceramics leads to a decrease in the processability of the composite material, and the dispersion and polarization are difficult. Therefore, the development of high-performance piezoelectric fiber sensing materials based on piezoelectric ceramics is difficult.

[0003] Therefore, how to overcome the difficulties in processing and polarization of high-performance piezoelectric sensing fibers and develop highly breathable piezoelectric fabrics based on these fibers is a technical problem that needs to be urgently solved in this field.

[0004] It should be noted that the above information disclosed in this background technology section is only used to understand the background technology of the present application concept, and therefore, the above description is not considered to constitute information of the prior art. Summary of the invention

[0005] The embodiments of the present disclosure at least provide a multi-layer coaxial piezoelectric sensing fiber and a preparation method thereof, and a flexible wearable fabric.

[0006] In a first aspect, an embodiment of the present disclosure provides a method for preparing a multilayer coaxial piezoelectric sensing fiber, comprising the following steps: step S1, preparing a core layer spinning solution and a shell layer spinning solution respectively, namely, weighing polyurethane and silane coupling agent, adding them to N, N-dimethylformamide, stirring and dissolving them, adding liquid metal after they are completely dissolved, and dispersing them into micro-nano particles by ultrasonic dispersion, the dispersion process is carried out in an ice bath, and the core layer spinning solution is obtained after the dispersion is complete; weighing lead zirconate titanate, adding them to N, N-dimethylformamide, ultrasonic dispersion, the dispersion process is carried out in an ice bath, and then the dispersed lead zirconate titanate suspension is stirred, and polyurethane and a silver precursor are added to the suspension, and stirring is continued until they are completely dissolved to obtain a shell layer spinning solution; step S2, placing the core layer spinning solution and the shell layer spinning solution on a wet spinning device, and sequentially extruding them into a coagulation bath through a metering pump and a coaxial needle for curing, drawing, and winding to obtain a composite fiber with a core-sheath structure; step S3, immersing the composite fiber in a reducing agent solution to reduce the Ag in the silver precursor. + Gradually migrate to the fiber surface and fully react with the reducing agent to generate nanosilver, which is stacked on the surface to form a composite piezoelectric layer. After washing away the excess reducing agent, a conductive fiber with a multi-layer coaxial structure is obtained; step S4, placing the conductive fiber in silicone oil, with the core layer of the fiber as the inner electrode, and the silver layer on the fiber surface as the outer electrode, and performing corona polarization treatment on the middle composite piezoelectric layer to obtain a self-generating sensor fiber; step S5, after mixing the polydimethylsiloxane main agent and the curing agent as a coating material, the polarized sensor fiber is encapsulated by dip coating to obtain a self-generating sensor fiber.

[0007] In an optional embodiment, in the step S1, the mass ratio of liquid metal and polyurethane added to the core layer spinning solution prepared is (2-4):1; the mass ratio of polyurethane and N,N-dimethylformamide added is 1:(5-10); and the mass ratio of silane coupling agent and polyurethane added is (1-2):100.

[0008] In an optional embodiment, in the step S1, the mass ratio of lead zirconate titanate and polyurethane added to the shell spinning solution prepared is (0.7-1.5):1; the mass ratio of polyurethane and N,N-dimethylformamide added is 1:(4-8); and the mass ratio of silver precursor and polyurethane added is (0.5-1.5):1.

[0009] In an optional embodiment, the power of the ultrasonic dispersion for preparing the core layer spinning solution in step S1 is 600-900W, the duration is 10-30min; and the ambient temperature of the ultrasonic dispersion is lower than 4°C; the power of the ultrasonic dispersion for preparing the shell layer spinning solution is 800-1100W, the duration is 20-40min; and the ambient temperature of the ultrasonic dispersion is lower than 4°C.

[0010] In an optional embodiment, the silane coupling agent in step S1 includes any one or more combinations of amino, epoxy, thiol, isocyanate and urea silanes; the silver precursor includes any one or more combinations of silver nitrate, silver acetate, silver trifluoroacetate and silver citrate.

[0011] In an optional embodiment, the ratio of the extrusion speed of the core layer spinning solution and the shell layer spinning solution in step S2 is (0.5-2):1.

[0012] In an optional embodiment, the reducing agent in step S3 includes any one or more combinations of formaldehyde, glyoxal, ethylenediamine, glucose, potassium sodium tartrate, sodium citrate, hydrazine hydrate, vitamin C, sodium borohydride and ascorbic acid; and the concentration of the reducing agent is 0.05-0.3 mol / L.

[0013] In an optional embodiment, in step S4, the polarization voltage is 6-15 kV / mm, the polarization temperature is 80-140° C., and the polarization time is 2-10 h.

[0014] In a second aspect, an embodiment of the present disclosure also provides a multilayer coaxial piezoelectric sensing fiber prepared by the method described above, comprising: from the inside to the outside, an inner electrode, a composite piezoelectric layer and an outer electrode; wherein the inner electrode comprises a liquid metal composite, the composite piezoelectric layer comprises a piezoelectric ceramic composite, and the outer electrode comprises nanosilver particles.

[0015] In a third aspect, an embodiment of the present disclosure also provides a flexible wearable fabric, which is made of the multi-layer coaxial piezoelectric sensing fiber as described above; wherein the processing method includes any one or more combinations of knitting, weaving, braiding and embroidery.

[0016] The beneficial effects of the present invention are that the multi-layer coaxial piezoelectric sensing fiber and its preparation method, and the flexible wearable fabric directly prepare the piezoelectric sensing fiber by a coaxial wet spinning method, thereby overcoming the problem that the multi-layer membrane structure piezoelectric sensor is not air-permeable; at the same time, a fiberized liquid metal composite is used as the inner electrode of the core layer, and an in-situ reduction method is used to migrate silver ions in the composite system to form an outer electrode of the shell layer. After the fiber is polarized, it can be used as a self-generating sensor, and the piezoelectric sensing signal output is stronger and more stable. After being processed into a flexible wearable fabric, it has a wider application.

[0017] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention are realized and obtained by the structures particularly pointed out in the description and the drawings.

[0018] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 A cross-sectional microstructure diagram of a PZT composite piezoelectric layer of a multi-layer coaxial piezoelectric sensing fiber provided in an embodiment of the present disclosure at a magnification of 2000 times; Figure 2 A cross-sectional microstructure diagram of the PZT composite piezoelectric layer of a multi-layer coaxial piezoelectric sensing fiber provided in an embodiment of the present disclosure at a magnification of 25,000 times. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] As used herein, the phrases "in one embodiment," "according to one embodiment," "in some embodiments," and the like generally refer to the fact that the particular feature, structure, or characteristic following the phrase may be included in at least one embodiment of the present disclosure. Therefore, a particular feature, structure, or characteristic may be included in more than one embodiment of the present disclosure, so that these phrases do not necessarily refer to the same embodiment. As used herein, the terms "example," "exemplary," and the like are used to "serve as an example, instance, or illustration." Any implementation, aspect, or design described herein as "example" or "exemplary" is not necessarily to be construed as preferred or superior to other implementations, aspects, or designs. On the contrary, the use of the terms "example," "exemplary," and the like is intended to present concepts in a concrete manner.

[0023] Herein, example embodiments of the present disclosure will be described in more detail with reference to the accompanying drawings. As used herein, expressions such as "at least one of..." modify the entire list of elements when following a list of elements, rather than modifying individual elements in the list. For example, the expression "at least one of a, b, and c" should be understood to include only a, only b, only c, both a and b, both a and c, both b and c, or all of a, b, and c.

[0024] The terms used herein are only used to describe specific exemplary configurations and are not intended to be limited. As used herein, the singular articles "one", "an" and "the" may also be intended to include plural forms, unless it is clearly indicated above that this is not the case. The terms "comprise", "include" and "have" are inclusive, and therefore specify the presence of features, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, elements, components and / or combinations thereof. The method steps, processes and operations described herein should not be interpreted as necessarily requiring them to be performed in the specific order discussed or shown, unless specifically identified as an execution order. Additional or alternative steps may be adopted.

[0025] In the existing published patents, most of the piezoelectric sensing materials are multilayer film materials, which do not have the air permeability and moisture permeability required for flexible wearables. The currently published piezoelectric sensing fibers mostly use some self-polarized piezoelectric materials (such as zinc oxide, barium titanate, polyvinylidene fluoride, etc.).

[0026] Specifically, piezoelectric polymers (polyvinylidene fluoride, etc.) are used as the matrix, formed by electrospinning, and inorganic piezoelectric powders (zinc oxide, barium titanate, etc.) are added to enhance the piezoelectric effect. Since the piezoelectric effect of self-polarized piezoelectric materials is weak and easily depolarized, the signal output intensity of the obtained piezoelectric fibers is generally weak, and their applications are limited.

[0027] In addition, all of the above piezoelectric sensing fibers need to be connected to electrodes before they can be used. Patent No. CN 116716680A discloses a coaxial wet-spun multifunctional fiber and its preparation method and application. A two-dimensional titanium carbide / polyvinyl alcohol@aramid nanofiber aerogel fiber with a skin-core structure is prepared by a one-step method. However, when the fiber is used as a sensing fiber, it still needs to be connected to electrodes and does not have the ability to generate electricity by itself.

[0028] The defects existing in the above solutions are the results obtained by the inventor after practice and careful research. Therefore, the discovery process of the above problems and the solutions proposed by the present disclosure for the above problems below should be the contributions made by the inventor to the present disclosure during the disclosure process.

[0029] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.

[0030] Some embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0031] The embodiment of the present disclosure provides a method for preparing a multilayer coaxial piezoelectric sensing fiber, comprising the following steps: Step S1, preparing a core layer spinning solution and a shell layer spinning solution respectively, namely, weighing polyurethane and silane coupling agent, adding them to N, N-dimethylformamide, stirring and dissolving them, adding liquid metal after they are completely dissolved, and using ultrasound to disperse them into micro-nano particles, the dispersion process is carried out in an ice bath, and after the dispersion is complete, the core layer spinning solution is obtained; weighing lead zirconate titanate, adding them to N, N-dimethylformamide, and ultrasonically dispersing them, the dispersion process is carried out in an ice bath, and the core layer spinning solution is obtained after the dispersion is complete; weighing lead zirconate titanate, adding them to N, N-dimethylformamide, and ultrasonically dispersing them, the dispersion process is carried out in an ice bath The step S2 is to place the core layer spinning solution and the shell layer spinning solution on a wet spinning device, extrude them into a coagulation bath through a metering pump and a coaxial needle in turn for solidification, drawing, and winding to obtain a composite fiber with a core-sheath structure; the step S3 is to immerse the composite fiber in a reducing agent solution to reduce the Ag in the silver precursor. + Gradually migrate to the fiber surface and fully react with the reducing agent to generate nanosilver, which is stacked on the surface to form a composite piezoelectric layer. After washing away the excess reducing agent, a conductive fiber with a multi-layer coaxial structure is obtained; step S4, placing the conductive fiber in silicone oil, with the core layer of the fiber as the inner electrode, and the silver layer on the fiber surface as the outer electrode, and performing corona polarization treatment on the middle composite piezoelectric layer to obtain a self-generating sensor fiber; step S5, after mixing the polydimethylsiloxane main agent and the curing agent as a coating material, the polarized sensor fiber is encapsulated by dip coating to obtain a self-generating sensor fiber.

[0032] In some embodiments, specifically, in the step S1, the mass ratio of liquid metal and polyurethane added to the core layer spinning solution prepared is (2-4):1; the mass ratio of polyurethane and N,N-dimethylformamide added is 1:(5-10); and the mass ratio of silane coupling agent and polyurethane added is (1-2):100.

[0033] In some embodiments, specifically, in the step S1, the mass ratio of lead zirconate titanate and polyurethane added to the shell spinning solution prepared is (0.7-1.5):1; the mass ratio of polyurethane and N,N-dimethylformamide added is 1:(4-8); and the mass ratio of silver precursor and polyurethane added is (0.5-1.5):1.

[0034] In some embodiments, specifically, the power of the ultrasonic dispersion for preparing the core layer spinning solution in step S1 is 600-900W, and the duration is 10-30min; and the ambient temperature of the ultrasonic dispersion is lower than 4°C; the power of the ultrasonic dispersion for preparing the shell layer spinning solution is 800-1100W, and the duration is 20-40min; and the ambient temperature of the ultrasonic dispersion is lower than 4°C.

[0035] In some embodiments, specifically, the silane coupling agent in step S1 includes any one or more combinations of amino, epoxy, thio, isocyanate and urea silanes; the silver precursor includes any one or more combinations of silver nitrate, silver acetate, silver trifluoroacetate and silver citrate.

[0036] In some embodiments, specifically, the ratio of the extrusion speed of the core layer spinning solution and the shell layer spinning solution in step S2 is (0.5-2):1.

[0037] In some embodiments, specifically, the reducing agent in step S3 includes any one or more combinations of formaldehyde, glyoxal, ethylenediamine, glucose, potassium sodium tartrate, sodium citrate, hydrazine hydrate, vitamin C, sodium borohydride and ascorbic acid; and the concentration of the reducing agent is 0.05-0.3 mol / L.

[0038] In some embodiments, specifically, in step S4, the polarization voltage is 6-15 kV / mm, the polarization temperature is 80-140° C., and the polarization time is 2-10 h.

[0039] The embodiment of the present disclosure also provides a multilayer coaxial piezoelectric sensing fiber prepared by the method as described above, comprising: from the inside to the outside, an inner electrode, a composite piezoelectric layer and an outer electrode; wherein the inner electrode comprises a liquid metal composite, the composite piezoelectric layer comprises a piezoelectric ceramic composite, and the outer electrode comprises nanosilver particles.

[0040] In some embodiments, specifically, the multilayer coaxial piezoelectric sensing fiber has a sensitivity range of 24.53-37.84 V / N, an average response time of no more than 58 ms, an air permeability of 110-160 mm / s, and a moisture permeability of 8500-9500 g / ㎡·24h.

[0041] The disclosed embodiment also provides a flexible wearable fabric, which is processed using the multi-layer coaxial piezoelectric sensing fiber as described above; wherein the processing method includes any one or more combinations of knitting, weaving, braiding and embroidery.

[0042] Example 1 Step S1, preparing a core layer spinning solution and a shell layer spinning solution respectively, that is, Weigh 100 parts of polyurethane and 1 part of silane coupling agent KH570, add them into 800 parts of N, N-dimethylformamide, stir and dissolve, add 250 parts of liquid metal after complete dissolution, use 1000W ultrasonic dispersion for 15 minutes to disperse into micro-nano particles, the dispersion process is carried out in an ice bath at 0°C, and after complete dispersion, a core layer spinning solution is obtained; Weigh 120 parts of lead zirconate titanate and add them to 700 parts of N, N-dimethylformamide for ultrasonic dispersion. Use 1000W ultrasonic dispersion for 20 minutes. The dispersion process is carried out in an ice bath at 0°C. Then, the uniformly dispersed lead zirconate titanate suspension is placed on a stirrer and stirred rapidly. At the same time, 100 parts of polyurethane and 100 parts of silver trifluoroacetate are added to the suspension. Stirring is continued until they are completely dissolved to obtain a shell spinning solution. Step S2, placing the core layer spinning solution and the shell layer spinning solution on a wet spinning device, and sequentially extruding them into a coagulation bath through a metering pump and a coaxial needle for solidification, drawing, and winding, the extrusion speeds of the core layer spinning solution and the shell layer spinning solution are 5 m / min and 4 m / min, respectively, to obtain a composite fiber with a core-sheath structure; Step S3, immersing the composite fiber in a reducing agent ascorbic acid solution to reduce the Ag in the silver precursor. + Gradually migrate to the fiber surface and fully react with the reducing agent to generate nanosilver, which is piled up on the surface to form a composite piezoelectric layer. After washing away the excess reducing agent, a multi-layer coaxial conductive fiber is obtained. Step S4, placing the conductive fiber in silicone oil, using the core layer of the fiber as the inner electrode and the silver layer on the surface of the fiber as the outer electrode, performing corona polarization treatment on the middle composite piezoelectric layer, the voltage of the polarization treatment is 25 kV, the temperature is 150° C., and the time is 6 hours, to obtain a self-generating sensor fiber; Step S5, after the polydimethylsiloxane main agent and the curing agent are mixed, the mixture is used as a coating material, and the polarized sensing fiber is packaged by a dip coating method to obtain a Figure 1 and Figure 2 The self-generating sensing fiber shown.

[0043] Example 2 Step S1, preparing a core layer spinning solution and a shell layer spinning solution respectively, that is, Weigh 100 parts of polyurethane and 1 part of silane coupling agent KH550, add them into 800 parts of N, N-dimethylformamide, stir and dissolve, add 200 parts of liquid metal after complete dissolution, use 800W ultrasonic dispersion for 15 minutes to disperse into micro-nano particles, the dispersion process is carried out in an ice bath at 8°C, and after complete dispersion, a core layer spinning solution is obtained; Weigh 100 parts of lead zirconate titanate and add them to 700 parts of N, N-dimethylformamide for ultrasonic dispersion. Use 800W ultrasonic dispersion for 20 minutes. The dispersion process is carried out in an ice bath at 8°C. Then, the uniformly dispersed lead zirconate titanate suspension is placed on a stirrer and stirred rapidly. At the same time, 100 parts of polyurethane and 100 parts of silver nitrate are added to the suspension, and stirring is continued until they are completely dissolved to obtain a shell spinning solution. Step S2, placing the core layer spinning solution and the shell layer spinning solution on a wet spinning device, and sequentially extruding them into a coagulation bath through a metering pump and a coaxial needle for solidification, drawing, and winding, the extrusion speeds of the core layer spinning solution and the shell layer spinning solution are 5 m / min and 3 m / min, respectively, to obtain a composite fiber with a core-sheath structure; Step S3, immersing the composite fiber in a reducing agent sodium borohydride solution to reduce the Ag in the silver precursor. + Gradually migrate to the fiber surface and fully react with the reducing agent to generate nanosilver, which is piled up on the surface to form a composite piezoelectric layer. After washing away the excess reducing agent, a multi-layer coaxial conductive fiber is obtained. Step S4, placing the conductive fiber in silicone oil, using the core layer of the fiber as the inner electrode and the silver layer on the surface of the fiber as the outer electrode, performing corona polarization treatment on the middle composite piezoelectric layer, the voltage of the polarization treatment is 23 kV, the temperature is 170° C., and the time is 6 hours, to obtain a self-generating sensor fiber; Step S5, after the polydimethylsiloxane main agent and the curing agent are mixed, the mixture is used as a coating material, and the polarized sensing fiber is packaged by a dip coating method to obtain a self-generating sensing fiber.

[0044] Example 3 Step S1, preparing a core layer spinning solution and a shell layer spinning solution respectively, that is, Weigh 100 parts of polyurethane and 1 part of silane coupling agent KH570, add them into 800 parts of N, N-dimethylformamide, stir and dissolve, add liquid metal after it is completely dissolved, use 1000W ultrasonic dispersion for 15 minutes to disperse into micro-nano particles, the dispersion process is carried out in an ice bath at 0°C, and after complete dispersion, a core layer spinning solution is obtained; Weigh 150 parts of lead zirconate titanate and add them to 700 parts of N,N-dimethylformamide for ultrasonic dispersion. Use 1200W ultrasonic dispersion for 20 minutes. The dispersion process is carried out in an ice bath at 0°C. Then, the uniformly dispersed lead zirconate titanate suspension is placed on a stirrer and rapidly stirred. At the same time, 100 parts of polyurethane and 150 parts of silver trifluoroacetate are added to the suspension, and stirring is continued until they are completely dissolved to obtain a shell spinning solution. Step S2, placing the core layer spinning solution and the shell layer spinning solution on a wet spinning device, and sequentially extruding them into a coagulation bath through a metering pump and a coaxial needle for solidification, drawing, and winding, the extrusion speeds of the core layer spinning solution and the shell layer spinning solution are 5 m / min and 4 m / min, respectively, to obtain a composite fiber with a core-sheath structure; Step S3, immersing the composite fiber in a reducing agent hydrazine hydrate solution to reduce the Ag in the silver precursor. + Gradually migrate to the fiber surface and fully react with the reducing agent to generate nanosilver, which is piled up on the surface to form a composite piezoelectric layer. After washing away the excess reducing agent, a multi-layer coaxial conductive fiber is obtained. Step S4, placing the conductive fiber in silicone oil, using the core layer of the fiber as the inner electrode and the silver layer on the surface of the fiber as the outer electrode, performing corona polarization treatment on the middle composite piezoelectric layer, the voltage of the polarization treatment is 25 kV, the temperature is 160° C., and the time is 8 hours, to obtain a self-generating sensor fiber; Step S5, after the polydimethylsiloxane main agent and the curing agent are mixed, the mixture is used as a coating material, and the polarized sensing fiber is packaged by a dip coating method to obtain a self-generating sensing fiber.

[0045] Comparative Example 1 The material components are the same as those in Example 1, except that the electrospinning + hot pressing + multi-layer composite process provided by the patent publication CN118756432A is adopted.

[0046] Comparative Example 2 The material components are the same as those in Example 1, except that the electrospinning+ZnO+multilayer composite process provided by the patent publication CN113654577A is adopted.

[0047] Comparative Example 3 The material components are the same as those in Example 1, except that the electrospinning piezoelectric ceramics + multilayer composite process provided by the patent publication CN108827502A is used.

[0048] Comparative Example 4 The material components are the same as those in Example 1, except that the three-dimensional weaving provided by the patent publication CN219568187U is used.

[0049] Comparative Example 5 The material components are the same as those in Example 1, except that the template-assisted + sol-gel method provided in the open document "Science Advances" DOI: 10.1126 / sciadv.abf0795 is used.

[0050] Specifically, the material components used in Comparative Examples 1-6 are the same as those in Example 1, and the performance parameters are those of the preferred embodiment.

[0051] Specifically, the molding methods and properties of the sensing fibers of Examples 1-3 and Comparative Examples 1-6 are shown in Table 1 below.

[0052]

[0053] Specifically, the piezoelectric sensing fiber is directly prepared by the coaxial wet spinning method, and is prepared into a wearable fabric through post-processing, which overcomes the problem of airtightness of the current multi-layer composite membrane structure piezoelectric sensors provided in Comparative Examples 1-4, and meets the requirement of long-term wearing of the sensor in practical applications.

[0054] Specifically, the coaxial spinning combined with the in-situ reduction technology enables the simple and rapid prototyping of multi-layer coaxial piezoelectric fibers with their own inner electrode layer and outer electrode, making continuous production possible.

[0055] Specifically, the self-generating sensing performance of the fiber is achieved through piezoelectric polarization treatment, and the output of the piezoelectric sensing signal is stronger and more stable, thereby enhancing its durability in practical applications.

[0056] In summary, the multi-layer coaxial piezoelectric sensing fiber and its preparation method, and the flexible wearable fabric use the coaxial wet spinning method to directly prepare the piezoelectric sensing fiber, which overcomes the problem of airtightness of the multi-layer membrane structure piezoelectric sensor; at the same time, the fiberized liquid metal composite is used as the inner electrode of the core layer, and the in-situ reduction method is used to migrate silver ions in the composite system to form the outer electrode of the shell layer. After the fiber is polarized, it can be used as a self-generating sensor. The piezoelectric sensing signal output is stronger and more stable, and it has a wider application after being processed into a flexible wearable fabric.

[0057] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A method for preparing a multi-layer coaxial piezoelectric sensing fiber, characterized in that: The steps include: Step S1, preparing a core layer spinning solution and a shell layer spinning solution respectively, that is, Weighing polyurethane and silane coupling agent, adding them into N,N-dimethylformamide, stirring and dissolving, adding liquid metal after complete dissolution, dispersing into micro-nano particles by ultrasonication, the dispersing process is carried out in an ice bath, and obtaining a core layer spinning solution after complete dispersion; Weighing lead zirconate titanate and adding it to N,N-dimethylformamide for ultrasonic dispersion, the dispersion process is carried out in an ice bath, then stirring the dispersed lead zirconate titanate suspension, adding polyurethane and silver precursor to the suspension, and continuing to stir until they are completely dissolved to obtain a shell spinning solution; Step S2, placing the core layer spinning solution and the shell layer spinning solution on a wet spinning device, and sequentially extruding them into a coagulation bath through a metering pump and a coaxial needle for solidification, drawing, and winding to obtain a composite fiber with a core-sheath structure; Step S3, immersing the composite fiber in a reducing agent solution to reduce the Ag in the silver precursor. + Gradually migrate to the fiber surface and fully react with the reducing agent to generate nanosilver, which is piled up on the surface to form a composite piezoelectric layer. After washing away the excess reducing agent, a multi-layer coaxial conductive fiber is obtained. Step S4, placing the conductive fiber in silicone oil, using the core layer of the fiber as the inner electrode and the silver layer on the surface of the fiber as the outer electrode, and performing corona polarization treatment on the middle composite piezoelectric layer to obtain a self-generating sensor fiber; Step S5, after the polydimethylsiloxane main agent and the curing agent are mixed, the mixture is used as a coating material, and the polarized sensing fiber is packaged by a dip coating method to obtain a self-generating sensing fiber.

2. The preparation method according to claim 1, characterized in that In step S1, the core layer spinning solution is prepared The mass ratio of liquid metal and polyurethane added is (2-4):1; The mass ratio of polyurethane and N, N-dimethylformamide added is 1: (5-10); The added mass ratio of silane coupling agent and polyurethane is (1-2):

100.

3. The preparation method according to claim 1, characterized in that: In step S1, the shell spinning solution is prepared The added mass ratio of lead zirconate titanate and polyurethane is (0.7-1.5):1; The mass ratio of polyurethane and N,N-dimethylformamide added is 1:(4-8); The mass ratio of the silver precursor and the polyurethane added is (0.5-1.5):

1.

4. The preparation method according to claim 1, characterized in that: In step S1 The power of ultrasonic dispersion for preparing the core layer spinning solution is 600-900W, and the duration is 10-30min; and the ambient temperature of ultrasonic dispersion is lower than 4°C; The power of ultrasonic dispersion for preparing the shell spinning solution is 800-1100 W, and the duration is 20-40 min; and the ambient temperature of ultrasonic dispersion is lower than 4°C.

5. The preparation method according to claim 1, characterized in that: In step S1 The silane coupling agent includes any one or more combinations of amino, epoxy, thio, isocyanate and urea silanes; The silver precursor includes any one or more combinations of silver nitrate, silver acetate, silver trifluoroacetate and silver citrate.

6. The preparation method according to claim 1, characterized in that: In step S2 The ratio of the extrusion speed of the core layer spinning solution to the shell layer spinning solution is (0.5-2):

1.

7. The preparation method according to claim 1, characterized in that: In step S3 The reducing agent includes any one or more combinations of formaldehyde, glyoxal, ethylenediamine, glucose, sodium potassium tartrate, sodium citrate, hydrazine hydrate, vitamin C, sodium borohydride and ascorbic acid; and The reducing agent concentration is 0.05-0.3 mol / L.

8. The preparation method according to claim 1, characterized in that: In step S4 The polarization voltage is 6-15 kV / mm, the polarization temperature is 80-140℃, and the polarization time is 2-10h.

9. A multi-layer coaxial piezoelectric sensing fiber prepared by the method according to any one of claims 1 to 8, characterized in that: include: From inside to outside, they are inner electrode, composite piezoelectric layer and outer electrode; The inner electrode comprises a liquid metal composite, the composite piezoelectric layer comprises a piezoelectric ceramic composite, and the outer electrode comprises nano silver particles.

10. A flexible wearable fabric, characterized in that: It is made of the multi-layer coaxial piezoelectric sensing fiber as claimed in claim 9; wherein The processing method includes any one or more combinations of knitting, weaving, braiding and embroidery.

Citation Information

Patent Citations

  • Flexible piezoelectric pressure sensor and preparation method thereof

    CN108827502A

  • Coaxial wet spinning multifunctional fiber and preparation method and application thereof

    CN116716680A

  • All-fiber one-way moisture-conducting piezoelectric sensing fabric

    CN219568187U

  • Electrospinning skin-core single fiber with axially equivalent piezoelectric property as well as preparation method and application thereof

    CN105671685A

  • Ag NWs-coated BaTiO3 core-sheath composite piezoelectric photocatalytic material as well as preparation method and application thereof

    CN113713813A